The Paradigm of Islamic Prophetic Thought Perspective of Kuntowijoyo and Musa Asy'arie - Zaprulkhan, Zaprulkhan; Supriyanto, Supriyanto; iskandi, Iskandi; Kurniawan, Muhammad Irfanudin (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2023)
Abstract In Islam, a very well-known adage appears that the Qur'an will always be relevant to be applied at any time and place, shalih li kulli zaman wa makan. Departing from this adage, Muslim scientists from the classical era to today's contemporary era, always try to make contextual interpretation of the verses of the Qur'an so that the messages remain relevant in addressing every societal need according to their respective space and time. respectively. This was done by two Indonesian Muslim scholars, namely Kuntowijoyo and Musa Asy'arie. Both Kuntowijoyo and Musa Asy'arie share the same scientific commitment, namely responding to the challenges of the times by returning to the fundamental Islamic doctrines contained in the Qur'an. The two scholars carry a re-reading of the Islamic religion, especially the Qur'an, with a prophetic spirit or paradigm. This article discusses the prophetic thoughts of Islam Kuntowijoyo and Musa Asy'arie as well as the similarities and differences between the two by using contextualist, historical, and philosophical critical approaches.